Can We Barter Local Taxes for Maintaining Our Green? A Psychological Perspective - Theodorou, Annalisa; Panno, Angelo; Agrimi, Mariagrazia; Masini, Emanuela; Carrus, Giuseppe (Frontiers in Psychology, 2022)
Previous research highlighted that the desire for neighborhood improvement is an antecedent of the citizens’ involvement in green urban areas maintenance. Nevertheless, the topic of civic participation in the maintenance of green areas is not yet well developed in the literature and a link with local legislation is missing. We investigate the intention of participation in such maintenance through a web-based experiment. We hypothesize that stimuli of poor (vs. good) maintenance will be associated with a higher intention of contributing to the upkeep of green areas following the administrative barter law. The administrative barter is a law approved in Italy, which gives citizens the possibility of a reduction of local taxes in exchange for their involvement in the improvement of the territory. One hundred ninety-six participants (Mage = 33.81) were assigned randomly to good maintenance condition (n = 100) or poor maintenance condition (n = 96). The level of maintenance was manipulated through photographs of a neighborhood depicting good or poor maintenance of the urban green ornamentation. Results pointed out that people showed a greater willingness to engage in the improvement of green urban areas in the poor condition as compared to the good condition, according to the law of administrative barter. This study points out how local legislation may provide an incentive fostering citizens’ involvement in green urban areas maintenance.